COMMUNICATIVE NATURE OF LEGAL LANGUAGE - ZAWŁOCKI, Robert (Comparative Legilinguistics, 2013)
The paper presents the criminal law as a purposeful linguistic composition with a specific characteristics. The Author elaborates this conceptualization through a reference to the criminal law’s essence. Subsequently, bearing in mind the fact that a language is being a communication device, he conducts further analysis concerning the language of the criminal law’s addressees, lawmakers and, lastly, interpreters. The analysis made from the abovementioned assessment perspective leads to a conclusion that the lawmaker, extensively, does not legislate in a fully reasonable manner, i. e.: knowingly, reasonably, simply, understandably and rightfully. The criminal law parlance should be specifically attributed to serve as a measure fulfilling the criminal law’s objectives. Otherwise, not only criminal law’s effectiveness deteriorates, but it additionally negatively affects social relationships which it should actually protect. A citizen cannot be accused of breaching a duty to comply with a criminal law norm, when the norm objectively could not impact the citizen’s behavior, because of a faultiness of its medium. In the Author’s opinion, a significant part of current Polish substantial criminal law provisions (norms) are not expressed in an appropriate legal language, being contrary with a prerequisite of communicativeness. Therefore, those provisions should be amended.